Prevalence of occupational injuries and associated factors among small scale industry Workers in Harar Town, eastern Ethiopia - Debelu, Desi; Tolera, Sina Temesgen; Baraki, Negga; Mengistu, Dechasa Adare (Frontiers in Public Health, 2025)
BackgroundCurrently, small-scale industries pose significant risks for occupational injuries, particularly in developing countries, including Ethiopia. Despite this problem, there is limited evidence on the prevalence of occupation-related injuries in small-scale industries that can be utilized for proposing interventions. Therefore, this study aims to determine the prevalence of occupational injuries and associated factors among small-scale industry workers in Harar town, Ethiopia.MethodsA cross-sectional study employing a quantitative analysis was conducted in Harare town, Eastern Ethiopia, from March 12, 2023, to June 1, 2023. The source of population was all small-scale industry workers in Harar town, while the study population was workers working in selected small-scale industries. The sample size was determined based on the previous study finding reported 35.98% prevalence of occupational injuries. A simple random sampling method was employed to select the study participant, resulting in the inclusion of 639 participants in the study. Data were collected using pretested questionnaires and observational checklists, covering sociodemographic, occupational injuries, occupational health and safety practices, work environment, and behavioral related factors. The data were analyzed via SPSS version 22, and a p value of <0.05 was considered the cut-off point for statistical significance in multivariate analysis.ResultsOut of the 639 small-scale industry workers included in the current study, 634 provided a response, resulting in a 99.2% response rate. Among these workers, 417 workers (65.8%) reported exposure to occupational injuries at least once in their careers, of which 223 (35.2%) were exposed to injuries in the last 12 months. The most commonly injured body parts were the hands (34.11%), legs (29.13%), and fingers (26.69%). The study found a significant associations between occupational injuries and type of industry (AOR: 2.41, 95% CI: 1.07, 5.46), educational status (AOR: 2.49, 95% CI: 1.01, 2.83), training (AOR: 1.4, 95% CI: 1.35, 3.22), working space (AOR: 4.6, 95% CI: 2.62, 7.51), and workload (AOR: 2.88, 95% CI: 2.78, 11.64).ConclusionMore than six out of 10 workers experienced injuries during their careers, with more than one-third being injured in the last 12 months. Workers with lower educational status, have no training, working in poor working conditions, and with higher workloads are at high risk of exposure. This highlights the need for improving occupational health and safety practices, including tailored training and supportive supervision to reduce injury in small-scale industries.Originality/valueThe findings from this study will be important for concerned bodies aiming to improve the occupational health and safety practices in small-scale industries and enhance the safe practices by addressing the safety culture in the working environment and policy making process.